FEATURE-ORIENTED VARIABILITY MANAGEMENT IN PRODUCT LINE ENGINEERING. - Jaejoon Lee; Muthig, Dirk (Communications of the ACM, 2006)
The article discusses the techniques used in the software making industry that enable the explicit modeling and management of product line variability across the life cycle from problem to solution space. By creating software with feature modeling and variability design, customers can more easily customize the product for their particular needs. Several examples in different industrial contexts are provided. The authors also recommend some ideas that need to be further researched.